The degree to which primary grade teachers use mind maps in teaching and the obstacles to use from the point of view of female educational supervisors in the city of Mecca - Al-Qathami, Hala Khaled; Manasrah, Mohammad Ahmed (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to explore the importance of employing mind maps by primary grade teachers and the extent of their use in areas such as lesson planning, implementation, assessment, and identifying obstacles. The research adopted a descriptive survey approach, using a 42-item questionnaire divided into four domains, distributed to 32 educational supervisors in Makkah. Data were analyzed using SPSS. Results indicated that the use of mind maps by primary teachers was rated very highly (average of 2.34 out of 5). Among the four domains, lesson planning scored the highest (average 2.28), followed by lesson implementation (average 2.36), and lesson assessment (average 2.44), all rated very highly. Obstacles scored an average of 3.88, rated as high. No statistically significant differences were found at (α ≤ 0.05) in responses across the four domains based on qualifications or experience. The study recommended training programs for teachers and supervisors to enhance mind map skills, integrate mind maps into professional development programs, and train educators in planning and implementing lessons using this strategy.